Hybridization-based aptamer labeling using complementary oligonucleotide platform for PET and optical imaging. (September 2016) - Park, Jun Young; Lee, Tae Sup; Song, In Ho; Cho, Ye Lim; Chae, Ju Ri; Yun, Mijin; Kang, Hyungu; Lee, Jung Hwan; Lim, Jong Hoon; Cho, Won Gil; Kang, Won Jun
Abstract: Aptamers are promising next-generation ligands used in molecular imaging and theragnosis. Aptamers are synthetic nucleic acids that can be held together with complementary sequences by base-pair hybridization. In this study, the complementary oligonucleotide (cODN) hybridization-based aptamer conjugation platform was developed to use aptamers as the molecular imaging agent. The cODN was pre-labeled with fluorescent dye or radioisotope and hybridized with a matched sequence containing aptamers in aqueous conditions. The cODN platform-hybridized aptamers exhibited good serum stability and specific binding affinity towards target cancer cells both in vitro and in vivo . These results suggest that the newly designed aptamer conjugation platform offers great potential for the versatile application of aptamers as molecular imaging agents.